Cryptology and Network Security 10th International Conference, CANS 2011, Sanya, China, December 10-12, 2011. Proceedings - Lin, Dongdai; Tsudik, Gene.; Wang, Xiaoyun; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 10th International Conference on Cryptology and Network Security, CANS 2011, held in Sanya, China, in December 2011. The 18 revised full papers, presented were carefully reviewed and selected from 65 submissions. The book also includes two invited talks. The papers are organized in topical sections on symmetric cryptanalysis, symmetric ciphers, public key cryptography, protocol attacks, and privacy techniques.
Keywords: Computer science; Computer Communication Networks; Data protection; Data structures (Computer science).; Data encryption (Computer science).; Coding theory; Computational complexity; Computer Science; Data Encryption; Computer Communication Networks; Discrete Mathematics in Computer Science; Coding and Information Theory; Data Structures, Cryptology and Information Theory; Systems and Data Security